Central Bank Digital Currency: research streams – a literature review - Šapkauskienė, Alfreda; Prialgauskaitė, Ineta (Socialiniai tyrimai, 2023)
Each type of payment - whether it would be coins and notes, electronic bank transfer, or remittance via fractions of bitcoin - could lead to a considerable number of benefits, as well, could possess a substantial number of risks or even threats to the current financial system and stability. The relatively recent concept of payment - cryptocurrencies, especially central bank digital currencies (CBDCs) - from a historical point of view, remains a mystery with only a few central banks to date launching these particular digital currencies. Since fundamental decisions in the development of CBDCs are taking place nowadays, it highlights the importance of a thorough review of already existing theoretical research with a view to determining various assessments and blind spots, before introducing CBDCs in the wider markets and usage. The scientific literature about CBDC was analysed using an extensive and systematic study of available research publications, their categorization, and summarizing. The authors offer a new glance toward a systemization of available scientific literature with a focus on CBDC. This novel suggestion of dividing research areas supports the idea of the end-to-end product life-cycle and comes into four different groups: motivations, design features, demands, and final impact on monetary sovereignty and the financial system as a whole. The unknown level of CBDC’s demand or expression of design features encourages researchers to consider various theoretical implications before CBDC will be creating major shifts in the banking industry or financial ecosystem.